2017
DOI: 10.1159/000456009
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Allergic Rhinitis and/or Allergic Conjunctivitis Associate with <b><i>IL13</i></b> rs20541 Polymorphism in Finnish Adult Asthma Patients

Abstract: Background: Our aim was to observe factors associated with IL13 rs20541 polymorphism and other factors with or without allergic comorbidities such as subject-reported allergic rhinitis (AR) and/or allergic conjunctivitis (AC) symptoms in adult asthmatics. Methods: A population-based sample of Finnish adult asthma patients (n = 1,156) and matched controls (n = 1,792) filled in a questionnaire. Asthma was diagnosed based on a typical history of asthma symptoms and lung function tests. Skin prick tests with 17 ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
1
11
1
Order By: Relevance
“…24 In addition, we have previously detected in a smaller adult population that allergic rhinitis and/or allergic conjunctivitis (AR/AC) and polysensitization co-associate with adult asthma. 11 We found that the association between adult-onset asthma and allergic multimorbidity decreased with age. These findings of a stronger increase in asthma risk associated with allergic multimorbidity in the youngest group are in line with results from a Swedish study, showing that the prevalence of allergic asthma has increased during the past two decades, while the prevalence of nonallergic asthma has remained on a stable prevalence level.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…24 In addition, we have previously detected in a smaller adult population that allergic rhinitis and/or allergic conjunctivitis (AR/AC) and polysensitization co-associate with adult asthma. 11 We found that the association between adult-onset asthma and allergic multimorbidity decreased with age. These findings of a stronger increase in asthma risk associated with allergic multimorbidity in the youngest group are in line with results from a Swedish study, showing that the prevalence of allergic asthma has increased during the past two decades, while the prevalence of nonallergic asthma has remained on a stable prevalence level.…”
Section: Discussionmentioning
confidence: 69%
“…These observations were recently extending by considering conjunctivitis in addition to rhinitis and asthma; the study showed that increase in allergic multimorbidity, irrespective of the disease (rhinitis, conjunctivitis, and asthma) was associated with a significant increase in the number of IgE reactivities to respiratory allergens . In addition, we have previously detected in a smaller adult population that allergic rhinitis and/or allergic conjunctivitis (AR/AC) and polysensitization co‐associate with adult asthma …”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We have previously demonstrated that polysensitization and allergic rhinitis and/or allergic conjunctivitis (AR/AC) co‐associate with adult asthma population . Polysensitization is associated with higher morbidity among asthmatic children .…”
Section: Introductionmentioning
confidence: 99%
“…Polysensitization is associated with higher morbidity among asthmatic children . Despite the fact that AR causes significant work impairment, studies suggest that AR/AC would putatively not be associated with adult asthma morbidity . Yet, limited evidence exists on the effect of AR/AC or other risk factors for mortality among adult asthmatic patients …”
Section: Introductionmentioning
confidence: 99%